Literasi Museum Untuk Generasi Muda Melalui Atraksi Paspor Museum Taman Mini Indonesia Indah - Ciwuk Musiana Yudhawasthi; Asrul Nur Iman; Fadli Muhammad Atalarik; Keith Nico P. Ramos; Jaennalene T. Openda; Nazwa Syauqina; Diffa Isnaini Kay; Rezki Intan Permata Dewi (CV. ITTC INDONESIA, 2025)
In the digital era, museums need creatively packaged attractions to enhance cultural literacy and increase young people’s interest in visiting. Creating targeted attractions requires collaboration between museums and various stakeholders. Such collaborative attractions can be developed through a community service program that combines literacy, gamification, and digital campaigns with a social marketing approach. This community service activity aims to promote museums within the Taman Mini Indonesia Indah (TMII) through the Jejak Langkah Sejarah: Berpetualang dengan Paspor Museum program. The implementation involves two methods. The first is a participatory approach, which directly involves the community in the entire process, from problem identification, planning, and implementation to evaluation. This participatory collaboration engages communities, academics, and cultural influencers and is designed in the form of interactive challenges at three TMII museums. The collaboration also includes pre-event activities such as promotion and coordination. The second method is research-based, integrating the results of previous museum research conducted by Komunitas Jelajah into the design of the community service program. The results show that meaningful experiences—marked by high participant enthusiasm and a positive perception of museums as enjoyable and educational spaces—can encourage repeat visits. The social marketing approach in this activity successfully creates a value exchange between cultural experiences and the engagement of young audiences.